One-Copy Serializability with Snapshot Isolation under the Hood - Bornea, Mihaela A.; Hodson, Orion; Elnikety, Sameh; Fekete, Alan (ICDE 2011, 2011)
This paper presents a method that allows a replicated database system to provide a global isolation level stronger than the isolation level provided on each individual database replica. We propose a new multi-version concurrency control algorithm called, serializable generalized snapshot isolation (SGSI), that targets middleware replicated database systems. Each replica runs snapshot isolation locally and the replication middleware guarantees global one-copy serializability. We introduce novel techniques to provide a stronger global isolation level, namely readset extraction and enhanced certiﬁcation that prevents read-write and write-write conﬂicts in a replicated setting. We prove the correctness of the proposed algorithm, and build a proto-type replicated database system to evaluate SGSI performance experimentally. Extensive experiments with an 8 replica database system under the TPC-W workload mixes demonstrate the practicality and low overhead of the algorithm.